THE RULES OF JAPANESE VERBAL COMMUNICATION ETIQUETTE (World Bulletin of Social Sciences, 2024)
This research work investigates the features of the rules of japanese verbal communication etiquette , etiquette in dialogue, speech manners and the Japanese terms of realationship and address within and outside the family. One of the features of the Japanese language, closely related to both the social structure of society and culture, is unanimously recognized as the socalled forms of politeness, in Japanese –“keigo”, which literally means “reverent, respectful language.” To each Japanese has to use in any conversation to convey the same content, different words and even different grammatical forms, depending on who he is talking to and about. The term "forms of politeness" has become familiar, although more precisely, to speak here not about politeness (which is individual), but about etiquette, the rules of which are socially determined. The Japanese attach great importance to kato; one of the authors writes somewhat pompously: “Language is the flower of culture, keigo- is the flower of language.” In this area of language, the same opposition between “friend and foe” appears, but it is superimposed on another hierarchical opposition that is most important for Japanese society "superior - equal - inferior." That is, they act simultaneously horizontal and vertical relationships between people
Keywords: “Keigo”; politeness; phenomenon of language; addressive